The Red Pony Movie Still - Chas. K. Feldman Group Productions, Incorporated; Republic Pictures; Viacom/Paramount Pictures:::Creator::::::::::::
Fred Tiflin (Shepperd Strudwick) talking with Tom, aka Jody Tiflin (Peter Miles) while using a water pump. Alice Tiflin (Myrna Loy) looks on in the background. RESTRICTED USE